PENERAPAN MEDIA CARD SORT DALAM MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA SMP SWASTA YAYASAN PERGURUAN KELUARGA PEMATANG SIANTAR - Fitria Tanjung, Liza; Dianti Siboro, Thiur; Saragih, Marlindoaman (Program Studi Pendidikan Biologi, Fakultas Keguruan Dan Ilmu Pendidikan Universitas Simalungun, 2023)
This study aims to improve student learning motivation in Basic Culinary Arts by implementing Card Sort Media in class VII-2 at YPK Private Junior High School, Pematang Siantar. This study was quantitative with a Classroom Action Research design. The subjects were 30 students in class VII-2. The research design used was a classroom action research model, which used a cycle. Each cycle in the study included four components/stages: planning, implementation/action, observation, and reflection. The data collection instruments used were test questions to measure material mastery, teacher and student observation guides, and a motivational questionnaire to measure motivation to learn about Environmental Pollution. The data analysis technique used was quantitative analysis. The results showed that the application of card sort media can improve motivation to learn about Environmental Pollution. This is evidenced by the increase in student learning motivation in science, which initially fell into the moderate category, with an average motivation level of 55.93. After implementing card sorting in Cycle I, the average learning motivation score for Environmental Pollution reached 68.20, which is considered quite good. After improvements were made when each indicator was inserted into each step of the learning process, the average learning motivation score for Environmental Pollution in Cycle II reached 76.73, which is considered good. Furthermore, the results of the Environmental Pollution mastery test, which initially fell into the poor category, reached an average of 45.00. After interventions in Cycle I, the results of the material mastery test increased to an average of 70.16, which is considered quite good. Teacher improvements were made in the next stage to increase the average score obtained by students, resulting in a Cycle II material mastery test result of 83.16, which is considered very good.